Altered Ulnar Nerve Kinematic Behavior in a Cadaver Model of Entrapment. Issue 6 (June 2015) - Mahan, Mark A.; Vaz, Kenneth M.; Weingarten, David; Brown, Justin M.; Shah, Sameer B.
Abstract : BACKGROUND: Ulnar nerve entrapment at the elbow is more than a compressive lesion of the nerve. The tensile biomechanical consequences of entrapment are currently marginally understood. OBJECTIVE: To evaluate the effects of tethering on the kinematics of the ulnar nerve as a model of entrapment neuropathy. METHODS: The ulnar nerve was exposed in 7 fresh cadaver arms, and markers were placed at 1-cm increments along the nerve, centered on the retrocondylar region. Baseline translation (pure sliding) and strain (stretch) were measured in response to progressively increasing tension produced by varying configurations of elbow flexion and wrist extension. Then the nerves were tethered by suturing to the cubital tunnel retinaculum and again exposed to progressively increasing tension from joint positioning. RESULTS: In the native condition, for all joint configurations, the articular segment of the ulnar nerve exhibited greater strain than segments proximal and distal to the elbow, with a maximum strain of 28 ± 1% and translation of 11.6 ± 1.8 mm distally. Tethering the ulnar nerve suppressed translation, and the distal segment experienced strains that were more than 50% greater than its maximum strain in an untethered state. CONCLUSION: This work provides a framework for evaluating regional nerve kinematics. Suppressed translation due to tethering shifted the location of high strain from articular to more distal regions of the ulnar nerve. The authors hypothesize that deformation is thus shifted to a region of the nerve less accustomed to high strains, thereby contributing to the development of ulnar neuropathy.